2013 6th International Conference on Human System Interactions (HSI) 2013
DOI: 10.1109/hsi.2013.6577886
|View full text |Cite
|
Sign up to set email alerts
|

Design and older people's real issues: Experiences of an engineer assessing technology in the user's home

Abstract: Engineers tend to confine themselves to designing technology for users in the lab. The authors wished to explore exposure to the real-world technology needs of older people by assessing technology use (via a universal design questionnaire) in the older person's own home. Following a series of home visits to older people and interviewing them on technology use, the authors were exposed to a number of experiences obtainable only from such visits. These are reported on in this paper in a quasi-chronological order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…All participants were the members of the centre and having experiences in technology use especially as a mobile phone user. They were provided informed consent which identified that confidentiality would be assured, included written information about the aim of the study and the details for whom to contact for further information regarding the study [4]. All the participants were given clarifying information about their right to withdraw at any time with no personal consequences, and that participation was voluntary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were the members of the centre and having experiences in technology use especially as a mobile phone user. They were provided informed consent which identified that confidentiality would be assured, included written information about the aim of the study and the details for whom to contact for further information regarding the study [4]. All the participants were given clarifying information about their right to withdraw at any time with no personal consequences, and that participation was voluntary.…”
Section: Methodsmentioning
confidence: 99%
“…Conventionally, both technology-focused and older people represent older people as recipients of technologies. The most effective way in gaining a better understanding of technology use by older people is to have a direct contact and engage with older technology users through their participation in a project [4]. Early engagement in framing design work with elderly is not the only challenge, but also in motivating design teams to seek to work with older people [5].…”
Section: Introductionmentioning
confidence: 99%
“…By extending the TAM model, the Unified Theory of Acceptance and Use of Technology (UTAUT) incorporated, in addition to performance and ease of use, two new elements, namely social influences, the degree to which an individual considers the pressures by important others towards the use of the system and facilitating conditions, or the degree to which an individual perceives to be supported by infrastructures and organizations in the use of the system (Venkatesh et al, 2003). Regardless of problems that come to the fore as people age and the presence of facilitators and barriers to adoption, it is estimated that more than 50% of older people's problems with technology can be solved either through a more appropriate design or through education (Hermann et al, 2012). Training and familiar interaction may overcome the anxiety and the lack of comfort in using technology, typically associated with older people (Nikou, 2015).…”
Section: Anna Paola Codini Michelle Bonera Giuseppe Bertolimentioning
confidence: 99%